DEVELOPMENT OF CARBIDE AND NITRIDE CERAMICS OF INCREASED RESISTIBILITY - O. V. Roman (Litʹë i Metallurgiâ, 2005)
The developments of carbide and nitrite ceramics of high solidity are presented. It is shown that development of nanotechnology led to creation of thenanostructural ceramics, the composition of which is controlled on cluster level.